PENGARUH DIVERSIVIKASI PRODUK, PERPUTARAN MODAL KERJA DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS - Darman, La Sudarman (Politeknik Negeri Ambon, 2023)
Competition in the business world in Indonesia is experiencing rapid development along with the times, especially the transition from the era of globalization to the era of digitalization. Telecommunications companies are business entities engaged in Information and Communication Technology (ICT) services and telecommunications networks in Indonesia. This study aims to analyze product diversification, working capital turnover and firm size on the profitability (ROA) of telecommunications sub-sector companies for the period 2016-2021. The sample in this study is the telecommunications sub-sector companies. This research uses multiple linear regression analysis method with the help of eviews version 9. The independent variables in this study are product diversification, working capital turnover and company size, and the dependent variable is profitability (ROA). The results show that partially product diversification has an effect on profitability, working capital turnover has no effect on profitability (ROA) and firm size has a significant negative effect on profitability (ROA) in telecommunications sub-sector companies for the 2016-2021 period.